Standardized Punica granatum Peel Extract Attenuates Adenine-Induced Chronic Kidney Disease in Rats: Effects on Renal Function, Oxidative Stress, Renal Histology, and Colon Morphology - Mathkal Mutlag, Shireen (Libyan Journal of Medical and Applied Sciences, 2026)
Chronic kidney disease (CKD) is defined by advancing renal impairment, structural kidney damage, oxidative dysregulation, and systemic metabolic anomalies. Adenine feeding is commonly employed to replicate CKD-like renal dysfunction and tubulointerstitial injury in rodents. This study assessed the efficacy of standardized Punica granatum peel extract (PPE) in alleviating adenine-induced chronic kidney disease (CKD) in rats. Methods: Rats were divided into six groups: normal control (NC), PPE-only, CKD control, CKD with low-dose PPE (CKD + PPE-L), CKD with high-dose PPE (CKD + PPE-H), and CKD with AST-120 reference treatment. The parameters examined included final body weight, food consumption, serum creatinine, serum urea, serum uric acid, renal malondialdehyde (MDA), reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), renal histology, and colon morphology. Adenine caused a CKD-like phenotype, as shown by lower body weight and food intake, higher levels of renal function-related parameters, higher levels of renal MDA, and lower levels of GSH, SOD, and CAT. PPE improved these abnormalities in a dose-responsive pattern, with high-dose PPE showing stronger restoration of renal function and antioxidant defense than low-dose PPE and generally comparable or superior effects to AST-120 for several measured endpoints. Renal H&E findings indicated severe tubular, glomerular, interstitial, and vascular injury in CKD controls, whereas PPE treatment reduced the severity of structural damage. Colon H&E descriptions showed CKD-associated epithelial erosion, crypt distortion, reduced goblet cell density, mucosal edema, and expanded lamina propria; PPE partially to markedly preserved mucosal architecture, particularly at the high dose.